The Effect of Utilitarian Web Browsing, Price Attribute, Sensory Attribute Toward Impulse Buying SME’s Product - Risca Kurnia Sari; Sudarmiatin Sudarmiatin; Agus Hermawan (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The phenomenon of online shops in the 4.0 industrial revolution is increasing, which makes online shopping sellers have to pay attention to variety of selection, price attributes, sensory attributes in order to increase impulse buying customer online of SME’s product. Purpose of this study is to determine the effect of variety of selection, price attributes, sensory attributes on impulse buying SME’s product Design/methodology/approach: This research is an explanatory research design. This type of research is a survey research, the number of respondents in this study was 200. The sample was taken using purposive sampling and using questionnaire method, then processed through SPSS software. The analytical tool in this study uses linear regression Findings: Only Sensory attribute has no significant effect on impulse buying SME’s product Research limitations/implications: This research has limitations, which is only in one city Practical implications: The practical implications of this research are as an enrichment of management knowledge, especially marketing and costumer behavior who buy SME’s products on digital platforms. Originality/value: The originality found in this study is research that focuses on SME’s products sold online in the industrial revolution 4.0 era Paper type: Research paper